Effect of Endothelin-1 on Baroreflexes and the Cardiovascular Action of Clonidine in Conscious Rabbits - Lim, Kyungjoon; van den Buuse, Maarten; Head, Geoffrey A. (Frontiers in Physiology, 2016)
We studied the influence of pretreatment with endothelin–1 on cardiac baroreflexes and on the effect of clonidine on blood pressure and heart rate. In order to avoid the complication of the direct vasoconstrictor effects of endothelin-1, initial dose-response studies in animals treated with a ganglion blocker were performed. Intravenous administration of 50, 200, and 1200 ng/kg of endothelin-1 produced biphasic changes in blood pressure, consisting of an immediate depressor response, followed by a long lasting and dose-dependent pressor effect (peak response 3 ± 1, 9 ± 3, and 33 ± 5 mmHg, respectively). Thus, the 50 ng/kg dose of endothelin-1 was used in subsequent studies. Conscious rabbits were pretreated on separate days with endothelin-1, either intravenously (50 ng/kg) or intracisternally (10 and 50 ng/kg), or with vehicle. The animals then received an intravenous dose (20 μg/kg) or an intracisternal dose (1 μg/kg) of clonidine and the effects on blood pressure and heart rate were measured. In vehicle-treated rabbits, the intravenous administration of clonidine induced a significant decrease in blood pressure and heart rate (15 min after injection: −15.7 ± 4.7 mmHg and −33 ± 4 b/min, respectively). Similarly, the intracisternal injection of clonidine lowered blood pressure (−16.0 ± 2.5 mmHg), but produced a less pronounced bradycardia (−18 ± 4 b/min). Endothelin pretreatment, either 50 ng/kg centrally or peripherally, had no significant effect on the hypotension or bradycardia produced either by central or peripheral injection of clonidine. At this dose, endothelin by itself did not produce significant changes in blood pressure or heart rate. There was a reduction of the gain of the baroreceptor-heart rate reflex with intracisternal endothelin-1. These results suggest that central 2–adrenoceptor mechanisms involved in clonidine-induced hypotension and bradycardia do not appear to be influenced by activation of endothelin receptors.